Thyroid hormone inhibits growth of hepatoma cells through induction of miR-214. Issue 1 (December 2017) - Huang, Po-Shuan; Lin, Yang-Hsiang; Chi, Hsiang-Cheng; Chen, Pei-Yu; Huang, Ya-Hui; Yeh, Chau-Ting; Wang, Chia-Siu; Lin, Kwang-Huei
Abstract Thyroid hormone (TH) plays a role in regulating the metabolic rate, heart functions, muscle control and maintenance of bones. 3, 3′5-tri-iodo-L-thyronine (T3 ) displays high affinity to nuclear thyroid hormone receptors (TRs), which mediate most TH actions. Recent studies have shown hypothyroidism in patients with an increased risk of hepatocellular carcinoma (HCC). MicroRNAs (miRNAs), a class of non-protein-coding RNA, are suggested to control tumor growth by interacting with target genes. However, the clinical significance of T3 /TR-regulated miRNAs in tumors has yet to be established. In the current study, miRNA expression profile screening was performed using SYBR Green-Based qRT-PCR array in TR-overexpressing HepG2 cells. miR-214-3p, which is expressed at low levels in HCC, was stimulated upon T3 application. The 3′UTR luciferase reporter assay confirmed that the proto-oncogene serine/threonine-protein kinase, PIM-1, is a miR-214-3p target. PIM-1 was decreased upon treatment with miR-214-3p or T3 stimulation. PIM-1 was highly expressed in HCC, and the effect of PIM-1 on cell proliferation might be mediated by the inhibition of p21. Furthermore, the T3 -induced suppression of cell proliferation was partially rescued upon miR-214-3p knockdown. Our data demonstrate that T3 induces miR-214-3p expression and suppresses cell proliferation through PIM-1, thus contributing to the inhibition of HCC tumor formation.